Iconoclasm and iconoclash: struggle for religious identity - Asselt, Willem J. van (Jewish and Christian perspectives series, 2007)
Preliminary Material /Willem Van Asselt , Paul Van Geest , Daniela Müller and Theo Salemink -- Introduction /Willem Van Asselt , Paul Van Geest , Daniela Müller and Theo Salemink -- 1. The Tension Between Word And Image In Christianity /Willemien Otten -- 2. The Dialectics Of The Icon: A Reference To God? /Anton Houtepen -- 3. Word And Image In Christian Rituals /Gerard Rouwhorst -- 4. Seeing The Divine: A Holy Controversy /Alexander Even-Chen -- 5. Our Image Of ‘Others’ And Our Own Identity /Daniela Müller -- 6. Idolatry And The Mirror: Iconoclasm As A Prerequisite For Inter-Human Relations /Marcel Poorthuis -- 7. Biblical Controversy: A Clash Between Two Divinely Inspired Messages? /Shulamit Laderman -- 8. Anthropomorphism And Its Eradication /Shamma Friedman -- 9. Augustine’S Thoughts On How God May Be Represented /Paul Van Geest -- 10. The Saint As Icon: Transformation Of Biblical Imagery In Early Medieval Hagiography /Nienke Vos -- 11. ‘Erant Enim Sine Deo Uero’: Iconoclash In Apocryphal And Liturgical Apostle Traditions Of The Medieval West /Els Rose -- 12. Tangible Words: Some Reflections On The Notion Of Presence In Gothic Art /Babette Hellemans -- 13. Cathars And The Representation Of The Divine: Christians Of The Invisible /Anne Brenon -- 14. The Clash Between Catholics And Cathars Over Veneration Of The Cross /Beverly Kienzle -- 15. Poor Building: The Case Of The Friars Minor /Gerard Pieter Freeman -- 16. The Prohibition Of Images And Protestant Identity /Willem Van Asselt -- 17. Aspects Of Iconoclasm In Utrecht Today And In The Past /Casper Staal -- 18. The Alphen Pig War /Joke Spaans -- 19. Papal Prohibitions Midway Between Rigor And Laxity. On The Issue Of Depicting The Holy Trinity /Jan Hallebeek -- 20. The Politics Of Representation: Prussian Monarchy And Roman Catholic Church In The Making Of Saints During The 19th Century /Angela Berlis -- 21. Christ, Art And The Nation. The Berlin ‘Christ Exhibition’ Of 1896 And The Search For A Protestant Identity In Wilhelminian Germany /Christopher König -- 22. The Written Icon: Images Of God In Modern Dutch Literature /Jaap Goedegebuure -- 23. The New Iconoclasm. The Avant-Garde And The Catholic Church /Theo Salemink -- 24. Vandalism As A Secular Iconoclasm /Alexander Demandt -- Index /Willem Van Asselt , Paul Van Geest , Daniela Müller and Theo Salemink -- Plates /Willem Van Asselt , Paul Van Geest , Daniela Müller and Theo Salemink -- Black And White Plates /Willem Van Asselt , Paul Van Geest , Daniela Müller and Theo Salemink.